Problems and prospects of modern civilizational development - Medzhidova, N.; Soloshchenko, P.P.; Zhakin, S.M. (Karagandy University of the name of acad. E.A. Buketov, 2022)
The article discusses the problems and prospects of modern civilizational development in the context of theoretical and practical attitudes of philosophical anthropology. Using the methodology of the activity approach, the authors reflect on the possibility of realizing the potential of philosophical research on the human problem in the processes of humanization of social activity. The authors, paying attention to the contradictory nature of the development of philosophical anthropology as a universal knowledge of the essence of man, bring to the fore the problem of understanding man as a unique biosociocultural system in its integral being. The modern organization of the social existence of mankind, as well as the modern type of culture, requires a scientific awareness of the place of man in the world and opens up new prospects for the development of philosophical anthropology. The current appeal to the theoretical and practical principles of philosophical anthropology is meant to address, first and foremost, those facets of human nature and life that distinguish a person as a significant and creative beginning of civilizational development, creating social and cultural forms of his or her being.
Қазіргі өркениеттік дамудың мəселелері мен перспективалары
Проблемы и перспективы современного цивилизационного развития
Keywords: man; philosophical anthropology; activity approach; humanism; symbiosis of sciences; civilizational development; philosophical thinking